Local distributions of multiplicative functions - Rimantas Skrabutėnas (Lietuvos Matematikos Rinkinys)
In the present paper the local distribution laws of values of multiplicative arithmetic functions g : G → R defined on arithmetical semigroups G and belonging to the class M(G) is considered. An asymptotical expansion for the main term in local limit theorem is obtained.